2017
DOI: 10.1007/s00705-017-3288-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of an Indian peste des petits ruminants virus isolate, Izatnagar/94, and its implications for virus diversity, divergence and phylogeography

Abstract: Peste des petits ruminants is an important transboundary disease infecting small ruminants. Genome or gene sequence analysis enriches our knowledge about the evolution and transboundary nature of the causative agent of this disease, peste des petits ruminants virus (PPRV). Although analysis using whole genome sequences of pathogens leads to more precise phylogenetic relationships, when compared to individual genes or partial sequences, there is still a need to identify specific genes/genomic regions that can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 76 publications
5
21
0
Order By: Relevance
“…A diverse nucleotide hotspot was obsereved between 5ʹ UTR of M and 3ʹ UTR of the F genes in the whole genome. This aligns with observations made previously where a hotspot was identified at similar position between M and F genes 14 , highlighting potential variations in the genome size and corresponding substitutions 43 in each of the gene. An influence of these spontaneous mutations in genome was assessed by employing Tajima's D statistics that showed a non-significant negative value for all coding genes in DnaSP analysis, suggesting a lack of influence of spontaneous mutations on the fitness of individual virus.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A diverse nucleotide hotspot was obsereved between 5ʹ UTR of M and 3ʹ UTR of the F genes in the whole genome. This aligns with observations made previously where a hotspot was identified at similar position between M and F genes 14 , highlighting potential variations in the genome size and corresponding substitutions 43 in each of the gene. An influence of these spontaneous mutations in genome was assessed by employing Tajima's D statistics that showed a non-significant negative value for all coding genes in DnaSP analysis, suggesting a lack of influence of spontaneous mutations on the fitness of individual virus.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to Table 10. Evidence of recombination events in the whole genome of Pakistan-originated SRMV strain along with breakpoint positions and significant p-values current study findings where analysis showed negative value for each of the coding genes, positive values in F and H genes has previously been suggested 14 . The non-synonymous/synonymous rate (ω = dN-dS) is an important indicator of selective pressure at the protein level where ω = 1 means neutral mutations, ω < 1 correspond to purifying selection while ω > 1 indicates diversifying positive pressure 44 .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A highly virulent PPRV (Izatnagar/94 - lineage IV) isolate maintained at PPR Laboratory, Division of Virology, Indian Veterinary Research Institute, Mukteshwar was used as a challenge virus (Sreenivasa et al, 2002). The accession number of this isolate is (KR140086.1; Sahu et al, 2017). Splenic suspension (10%) of virulent virus was inoculated subcutaneously (4 ml suspension, 2 ml each at two different sites).…”
Section: Methodsmentioning
confidence: 99%